Full sentence vs. substitutable defining formats: a study of translation equivalents - Fakharzadeh, Mehrnoosh; Mahdavi, Behnaz (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present article reports on the results of a study which investigated the quality of translation equivalence for mental verbs as guided by two monolingual dictionaries namely, the Oxford Advanced Learner’s Dictionary of Current English and the COBUILD Dictionary, which employ two distinct defining strategies, Substitutability and Full-Sentence strategies respectively. Two parallel tests were administered to a group of Persian translation trainees. In one of the tests, the unknown verbs were defined by Substitutability and in the other, by Full- Sentence Strategy. The results showed that the participants performed significantly better on the test the items of which were defined by Substitutability strategy. The analysis of the test items revealed that both definition formats are conducive to kidrule strategy which guided them to select familiar words from the entry as a substitute for the search term. The application of this strategy was also found to depend on the position of information content, information load, in the definitions.